The application of multi-criterion methods for valuation of recreation property/Die Anwendung der Mehrkriteriellen Methode bei der Bewertung von Erholungsgrundstücken - Zavadskas, Edmundas Kazimieras; Kaklauskas, Arturas; Raslanas, Saulius; Malienė, Vida (Journal of Civil Engineering and Management, 2001)
Multi-criterion valuation methods are widely used in real estate valuation all over the world. In USA, UK and other countries these methods are part of techniques based on comparative and reinstatement values as well as on income use [1]. A number of problems in the valuation of real property can be eliminated by the methods of multiple criteria analysis, which came into existence only at the second half of the 20th century. Currently, they have become very important in the international practice of the real property valuation. In most cases they are based on market modelling and economic assumptions. Therefore, sometimes they are referred to as separate valuation methods, and classified as modern ones. This article describes a new method of multiple criteria analysis. This method based on the market analysis and valuation principle is in line with the traditional comparative value method, therefore it can be attributed to the group of the indirect comparative value methods. These methods facilitate the universal and more extensive multiple criteria analysis of the property, since they take account of a number of different criteria, ie qualitative, quantitative ones, market conditions. The proposed method can meet the demands and needs of many interested groups since it enables to estimate not only the market value of the property, but also other values, eg investment value, value of use, market value of the current use of the property, etc. This article analyses the theoretical model of the method, which was used to estimate the market value of the recreation premises. Daugiakriterinio metodo taikymas poilsinėms sodyboms vertinti Santrauka. Visame pasaulyje nekilnojamojo turto vertinimo praktikoje plačiai taikomi daugiakriteriniai vertinimo metodai. JAV, JK ir kitose šalyse šie metodai yra vertinimo technologijų, pagrįstų verčių palyginimu, atkūrimu ir pajamų gavimu, sudėtinės dalys [1]. Daugiakriterinės analizės metodai buvo sukurti XX a. antrojoje pusėje. Juos taikant galima išvengti nemaža nekilnojamojo turto vertinimo problemų. Jie yra labai svarbūs tarptautinėje nekilnojamojo turto vertinimo praktikoje. Dažniausiai šie metodai pagrįsti rinkos modeliavimu ir ekonominėmis prielaidomis. Tačiau kartais jie taikomi atskirai ir priskiriami prie modernių vertinimo metodų. Aprašomas naujas daugiakriterinės analizės metodas. Jis grindžiamas rinkos analize ir vertinimo principais, lyginamas su tradiciniu lyginamosios vertės metodu, tačiau gali būti priskirtas prie netiesioginių lyginamosios vertės metodų. Pastarieji metodai padeda universaliau ir plačiau analizuoti turtą, aprašomą. įvairais kriterijais, pvz., kokybiniais, kiekybiniais bei rinkos sąlygomis. Siūlomas metodas gali būti taikomas ne tik suinteresuotų grupių paklausai ir pasiūlai, rinkos vertei nustatyti, bet ir nustatyti tokioms vertėms, kaip investavimo, naudojimo ir kt. Aprašomas metodo teorinis modelis, kuris buvo pritaikytas poilsinių sodybų rinkos vertei nustatyti. First Published Online: 30 Jul 2012